ä½¿ç”¨åŠ¨ç”»å›¾ç‰‡åª’ä½“æ•™å¦æé«˜å¦ç”Ÿçš„åè¯æŽŒæ¡èƒ½åŠ› - Muhamzah, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
æ‘˜è¦ï¼šåè¯æ˜¯æ±‰è¯è¯æ±‡ä¹‹ç±»ä¹‹ä¸€ã€‚è¿™ç±»è¯éƒ½è¡¨ç¤ºäººæˆ–äº‹ç‰©åç§°çš„è¯ã€‚åˆçº§é˜¶æ®µå¦ä¹ è€…åœ¨å¦ä¹ åè¯é‡åˆ°äº†ä¸å°‘çš„å›°éš¾ï¼Œå¤§éƒ¨åˆ†çš„å¦ç”Ÿå¾ˆéš¾è®°å¾—ä»–ä»¬æ‰€å¦è¿‡çš„åè¯, å› æ¤åè¯æ•™å¦æ˜¯å¯¹å¤–æ±‰è¯æ•™å¦ä¸é‡è¦çš„éƒ¨åˆ†ã€‚ç¬”è€…åœ¨å¤ç”¸Kemala Bhayangkariåˆä¸ Â å®žä¹ è¿‡ç¨‹ä¸å‘çŽ°å¦ç”Ÿå¯¹åè¯çš„æŽŒæ¡ä¸å¤Ÿå¥½ã€‚ä¸ºäº†æé«˜å¤ç”¸Kemala BhayangkariÂ åˆä¸äºŒçº§å¦ç”Ÿå¯¹åè¯çš„æŽŒæ¡èƒ½åŠ›ï¼Œç¬”è€…é€šè¿‡åŠ¨ç”»å›¾ç‰‡åª’ä½“æ•™å¦è¿›è¡Œåè¯çš„æ•™å¦ã€‚ é€šè¿‡å‰æµ‹ä¸ŽåŽæµ‹çš„å¯¹æ¯”ï¼Œç¬”è€…å‘çŽ°å¦ç”Ÿçš„å‰æµ‹å¹³å‡æˆç»©ä¸º52.22åˆ†ï¼Œè€Œå¦ç”Ÿçš„åŽæµ‹å¹³å‡æˆç»©æˆä¸º68.33åˆ†ï¼Œè¿™è¡¨æ˜Žå¦ç”Ÿå¯¹åè¯çš„æŽŒæ¡èƒ½åŠ›æé«˜äº†ã€‚ Â å…³é”®è¯ï¼šå‰¯è¯ åè¯ æŽŒæ¡èƒ½åŠ› åŠ¨ç”»å›¾ç‰‡åª’ä½“ Abstract : Â Noun is one of the word classification in Mandarin. Such words used to describe people or things. At the basic stage, learners face many difficulties in learning nouns. Most students have difficulty remembering the nouns theyÂ learned. Therefore, noun teaching is an important part of teaching Chinese as a foreign language. When the author had teaching at the Pontianak Kemala Bhayangkari junior high school pontianak found that students are not good enough in mastering the noun. To improve noun mastery of ability Kemala Bhayangkari secondary school students, the author used an animation teaching toll internship to teach nouns. Through the comparison of pre-tests and post-tests, make found that students averaged a score of pretest is 52.22% before and a score of post test is 68.33% that indicates that students have improvement in mastery noun. Keywords: adverbÂ Â Â Â Â Â Â Â nounÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â masteryÂ Â Â Â Â Â Â Â Â animation picture media